Предмет:
МатематикаАвтор:
анонимВ данном многочлене за скобки можно вынести x и x^2.
Выносим x:
1) -2 + 3x - 4x^2 + 5x^3 = -2 + x * ( 3 - 4x) + 5x^2;
2) -2 + 3x - 4x^2 + 5x^3 = -2 + 3x - x * (4x + 5x^2);
3) -2 + 3x - 4x^2 + 5x^3 = -2 + x * ( 3 - 4x + 5x^2).
Выносим x^2:
-2 + 3x - 4x^2 + 5x^3 = -2 + 3x - x^2 * (-4 + 5x).
Автор:
matteobxioДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть